Teachers and Students' Illocutionary Act in Bahasa Indonesia Subject - Wahyuni, Neneng (Jurnal KATA: Penelitian tentang Ilmu Bahasa dan Sastra, 2019)
This research describes the students' and teachers' illocutionary act in learning Indonesian at state senior high school number 1 of Payakumbuh. The object of the research was the students and teachers at SMAN 1 of Payakumbuh for Bahasa Indonesia subject. The research applied qualitative descriptive method in collecting and analyzing the data. The research shows that the illocutionary acts of students' of 11th grade and teacher's for Bahasa Indonesia subject acquired 61 speech acts, which are (1) 18 assertive, (2) 2 explanatory assertive, (3) 2 reporting assertive speech, (4) 21 directive utterance commanded which is consisted of 17 teacher’s utterances and 4 student’s utterances, (5) 4 directive requests begging, (6) 3 directive of advice, (7)) 2 directive reminding, (8 ) 2 directive asked for something (9) 6 accused expressive. (10) 4 expressive complained, and (11) 1 commissive promissing. In conclusion, most of illocutionary acts used towards teacher and the students at 11th grade for Bahasa Indonesia subject in SMAN 1 Payakumbuh was directive speech act. The rarely used speech act was commissive.